Endoscopic ultrasound-guided coil and glue for treatment of splenic artery pseudo-aneurysm: new kid on the block! - Rai, Praveer; KC, Harish; Goel, Amit; Aggarwal, Rakesh; Sharma, Malay (Endoscopy International Open, 2018)
Background and study aims Pseudoaneurysm most commonly involves the splenic artery and is conventionally treated with angioembolization or surgery. Herein we describe six patients with splenic artery pseudoaneurysm who were treated using a new technique of endoscopic ultrasound (EUS)-guided glue and coil injection. Patients and methods Six patients (median age 36.7, range: 19 – 60, M: F = 5:1) with splenic artery pseudoaneurysm who had failed angiographic embolization underwent EUS-guided transgastric injection of coil and glue injection between July 2016 and September 2017. Results The diameter of the splenic artery pseudoaneurysms varied from 2.5 cm to 6.5 cm. The size (8, 14 and 16 mm) and number (1 to 5) of coils and amount of glue (1 – 2 mL) injected all were greater in larger aneurysm. All six patients had complete occlusion of the pseudoaneurysm as determined by using computed tomography at 4 weeks and EUS at 12 weeks. No complication was encountered.Conclusion EUS-guided coil and glue injection for obliteration of splenic artery pseudoaneurysm is a feasible, highly effective and safe technique.